Delayed Recovery of Bilateral Supplementary Motor Area Syndrome After the Resection of a Central Neurocytoma - Gerald, Alasdair Fitz; Aneela, Irrum; Choszczewski, Paula; Summers, David; Kaliaperuma, Chandrasekaran (Biology, Engineering, Medicine and Science Reports)
Supplementary Motor Area (SMA) syndrome is a rare complication following brain tumor (localized in the supplementary motor area) removal and is characterized by temporary paralysis and mutism. These symptoms typically resolve within hours to days. This case report challenges the typical presentation of SMA Syndrome. We report a unique case where a patient developed right dense hemiplegia (severe weakness on one side of the body) and mutism after resection of an intraventricular central neurocytoma (a benign tumor within the brain's fluid-filled cavities). This deviates from the usual transient nature of SMA syndrome. This case report delves into the extended duration of these post-surgical symptoms in this patient. It compares the case with existing literature on SMA syndrome to understand the reasons behind this atypical presentation. By analysing similar cases, we aim to shed light on potential factors that might influence the severity and duration of recovery in SMA syndrome. This case highlights the importance of considering variations in SMA syndrome presentation. It emphasizes the need for further research to improve our understanding of the factors influencing recovery patterns after surgery in this region of the brain.
Keywords: Central neurocytoma; Supplementary motor area syndrome; Frontal aslant tract; Hemiplegia; Mutism